Characteristics of Clinical and Electrophysiological Pattern in a Large Cohort of Chinese Patients With Charcot-Marie-Tooth 4C - Duan, Xiaohui; Ma, Yan; Fan, Dongsheng; Liu, Xiaoxuan (Frontiers in Neurology, 2021)
The “Src homology 3 (SH3) domain and tetratricopeptide repeats 2” (SH3TC2) gene is mutated in individuals with Charcot-Marie-Tooth disease (CMT) and considered relevant to a demyelinating or intermediate subtype of CMT disease, CMT4C. In this study, we screened a cohort of 465 unrelated Chinese CMT patients alongside 650 controls. We used Sanger, next-generation, or whole-exome sequencing to analyze SH3TC2 and other CMT-related genes and identified 12 SH3TC2 variants (eight novel) in seven families. Of the eight novel variants, seven were likely pathogenic (c.280–2 A > G, c.732–1 G > A, c.1177+6 T > C, c.3328–1 G > A, G299S, R548W, L1048P), and 1 had uncertain significance (S221P). The CMT4C frequency was calculated to be 4.24% in demyelinating or intermediate CMT patients without PMP22 duplication. Additionally, we detected variant R954* in the Chinese cohort in our study, indicating that this variant may be present among Asians, albeit with a relatively low frequency. The onset age varied among the eight patients, three of whom presented scoliosis. We summarized phenotypes in the Chinese CMT cohort and concluded that the absence of scoliosis, cranial nerve involvement, or late-onset symptoms does not necessarily preclude SH3TC2 involvement in a given case.